The Extinction of Local Language: a Literature Psychology Review - Rosmawaty (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
This paper tries to discuss theoretically about the relationship between language and nationalism towards the extinction of local languages in Indonesia which has become a trend appearing in the movement in critical symptoms of dynomia that involves national culture and local culture with a literature psychology approach. The psychoanalytic review of the extinction of local languages is to view the extinction of language psychologically in the notion of macro functions of language according to Garvin and Mathiot (1956) who say that language as (1) unifying and (2) separator. Some implications in this paper are tried to be drawn: (1) local culture (theoretically) will also become extinct along with the extinction of local languages; (2) the possibility of the provincialism emergence (and the implication of the separatist movements) is reduced: (3) The cost of maintaining the local languages can be eliminated and the cost of learning the national language can be concentrated on planning and learning Indonesian language so that this language reaches the level of a modern and effective language; (5) all efforts can be concentrated against the domination of English over the national language; (6) the sense of nationality of the Indonesian people will become stronger, and (7) cultural diversity will decrease. Without such policies, languages can die or become extinct naturally. In this case, the cause is the existence of language competition and the competition that used to be monolingual.